Children`'s Health is Insulin and Lipid Dependent - Hydrie, M.Z.I.; Basit, A.; Ahmadani, M.Y.; Masood, M.Q. (Pakistan Journal of Nutrition, 2004)
To assess the differences in fasting blood glucose, insulin and lipids of children having family history of diabetes or heart disease in first or second degree relative compared with a control group. Questionnaire was given to collect demographic data and to assess the dietary habits and family history of these children. Demographic data, anthropometric measurements and blood samples for fasting blood glucose, insulin and lipids of children from 4 schools was taken. The samples of ninety nine children were collected and sent to Baqai Institute of Diabetology and Endocrinology, Karachi to assess their biochemical parameters. Children having positive family history for diabetes had slightly mean values for BMI as compared to the controls but the differences were not statistically significant. Overweight risk children (>85th Percentile of BMI for age) did not differ significantly in terms of various risk indicators however those who had a positive family history of diabetes had significantly higher percentage of abnormal Total Cholesterol, LDL-C, Insulin and low HDL. Diabetes and CVD risks in children having positive family history are probably mediated through increased weight. Thus information about family history augmented by body mass index could be used as an important screening tool for determining the risk status of children.